Diversidade sexual e ensino de ciências: buscando sentidos - Coelho, Leandro Jorge [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The aim of this study was to analyze the meanings attributed by Science teachers and students to sexual diversity. We used the categories significance and meaning, adopting the Cultural-Historical Psychology. Many meanings established socio historically about sexuality refer to the exclusion, marginalization and stigmatization of Lesbian, Gay, Bisexual and transgender people because of their sexual orientations and gender identities that are somehow against the heterosexist standard socially accepted as natural. Intentionally or not, school, is one of the places where the (re) affirmation of these significances and meanings about sexual diversity occurs. Science teachers are recognized by parents, students and other colleagues as able and prepared to deal with issues related to sexuality, becoming central actors to the discussion of the relationship between school and sexual diversity. This way a qualitative study and we used questionnaires, interviews, text productions, documentary analysis and the focus group technique. Two science teachers were interviewed, 106 students responded to a questionnaire, 115 participated in the production of a text and 27 went to the Focus Groups. Generally, students consider LGBT people as weird, even though many of then believe they have a duty to respect everyone's choices. Transvestites were reportedly presented with disapproval by some students, and homosexuality and bisexuality apparently are more accepted, but still considered weird. Teachers recognize LGBT identities and the existance of prejudice against these individuals. They indicate to believe their students are prejudiced when it comes to sexual diversity. Meanings of the media and religion seem to influence the construction of meaning from students about sexual diversity, as show by their reports and the statements of their teachers. Heteronormative meanings are expressed by many students regarding sexual diversity, but some of them indicate...

O objetivo desta estudo foi analisar os sentidos atribuídos por professores de Ciências e alunos à diversidade sexual. Para isso, utilizamos as categorias sentido e significado, adotando o referencial da Psicologia Histórico-Cultural. Com relação à sexualiade, muitos significados estabelecidos sócio historicamente remetem à exclusão, estigmatização e marginalização de Lésbicas, Gays, Bissexuais e Transgêneros, por suas orientações sexuais e identidades de gênero que fogem ao padrão heterossexista socialmente difundido e aceito como natural. De maneira intencional ou não, a escola é um dos lugares em que ocorre a (re)construção de significados e sentidos com relação à diversidade sexual. Os professores de Ciências são reconhecidos por pais, alunos e demais colegas como profissionais aptos e preparados para tratar de questões relacionadas à sexualidade, assumindo um papel importante quando se discute as relações entre escola e diversidade sexual. Esse foi um estudo qualitativo em que foram utilizados questionários, entrevistas, produção de textos, análise documental e a técnica de grupo focal para a coleta de dados. Dois professores de Ciências foram entrevistados e 106 alunos responderam a um questionário, 115 participaram da produção de um texto e de vinte e sete dos Grupos Focais. De modo geral, os alunos possuem sentidos que assumem LGBT como estranhos, mesmo muitos acreditando terem o dever de respeitar as escolhas de cada um. As travestis foram declaradamente apresentadas com repúdio por eles, sendo a homossexualidade e bissexualidade aparentemente mais aceitas, mesmo sendo consideradas estranhas. Os professores reconhecem as identidades LGBT e o preconceito existente contra esses indivíduos. Significados religiosos e outros veiculados pela mídia parecem influenciar a construção de sentidos dos alunos sobre a diversidade sexual, como mostram seus relatos e as falas dos professores...
Keywords: Educação sexual; Ciencia; Ensino; Orientação sexual; Pessoas LGBT; Sex instruction